Participatory co-design and normalisation process theory with staff and patients to implement digital ways of working into routine care: the example of electronic patient-reported outcomes in UK renal services - S. E. Knowles; A. Ercia; F. Caskey; M. Rees; K. Farrington; S. N. Van der Veer (BMC, 2021)
Abstract Background Successful implementation of digital health systems requires contextually sensitive solutions. Working directly with system users and drawing on implementation science frameworks are both recommended. We sought to combine Normalisation Process Theory (NPT) with participatory co-design methods, to work with healthcare stakeholders to generate implementation support recommendations for a new electronic patient reported outcome measure (ePRO) in renal services. ePROs collect data on patient-reported symptom burden and illness experience overtime, requiring sustained engagement and integration into existing systems. Methods We identified co-design methods that could be mapped to NPT constructs to generate relevant qualitative data. Patients and staff from three renal units in England participated in empathy and process mapping activities to understand 'coherence' (why the ePRO should be completed) and 'cognitive participation' (who would be involved in collecting the ePRO). Observation of routine unit activity was completed to understand 'collective action' (how the collection of ePRO could integrate with service routines). Results The mapping activities and observation enabled the research team to become more aware of the key needs of both staff and patients. Working within sites enabled us to consider local resources and barriers. This produced 'core and custom' recommendations specifying core needs that could be met with customised local solutions. We identified two over-arching themes which need to be considered when introducing new digital systems (1) That data collection is physical (electronic systems need to fit into physical spaces and routines), and (2) That data collection is intentional (system users must be convinced of the value of collecting the data). Conclusions We demonstrate that NPT constructs can be operationalised through participatory co-design to work with stakeholders and within settings to collaboratively produce implementation support recommendations. This enables production of contextually sensitive implementation recommendations, informed by qualitative evidence, theory, and stakeholder input. Further longitudinal evaluation is necessary to determine how successful the recommendations are in practice.